POLYCRYSTAL SiC MOLDED ARTICLE
By controlling the CVD reaction conditions, a polycrystalline SiC molded body with an average crystal particle size and nitrogen concentration within a specific range was prepared, which solved the problems of wear and high resistivity, and was suitable for use in heaters and other purposes in semiconductor manufacturing devices.
Patent Information
- Application Number
- CN202480003471.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-08-25
- Filing Date
- 2024-06-03
- Publication Date
- 2025-04-25
AI Technical Summary
The crystal particle size of the existing polycrystalline SiC molded bodies is small, resulting in particulate matter generated during wear and high volume resistivity, making them not suitable for use in heaters and other applications in semiconductor manufacturing devices.
By controlling the CVD reaction conditions, including adjusting the film formation speed, residence time and nitrogen gas doping, a polycrystalline SiC molded body with an average crystal particle size of 5.5 μm or more than 25.0 μm, a nitrogen concentration of 0.27 × 1020/cm3 or more than 5.4 × 1020/cm3 or less, and a product of carrier density and Hall mobility is 4.0 × 1020/cmVsec or more than 100 × 1020/cmVsec or less.
A polycrystalline SiC molded body with a crystal particle size within a specific range has been realized, and the volume resistivity is reduced to less than 0.0200Ω·cm, and is suitable for use in heaters and other purposes in semiconductor manufacturing devices.
Smart Images

Figure CN119895074A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a polycrystalline SiC molded body and a method for producing the same. Background Art
[0002] Polycrystalline SiC (silicon carbide) molded bodies have excellent mechanical strength characteristics, electrical characteristics, heat resistance, chemical stability, etc., and are used for various industrial purposes. For example, polycrystalline SiC molded bodies are used in high-temperature atmospheres and high-purity atmospheres. As common uses, there are: virtual wafers, semiconductor manufacturing equipment components such as components constituting semiconductor manufacturing equipment, etc.
[0003] For example, a polycrystalline SiC molded body used as a component of a semiconductor manufacturing device is generally in the form of a plate.
[0004] The polycrystalline SiC molded body takes the growth direction of the CVD film as the main surface. If it is a plate-shaped polycrystalline SiC molded body, the surface and the back surface other than the side surface can become the main surface. The thickness of the polycrystalline SiC molded body changes with the film forming time and can be formed into any thickness. It is known that there is a polycrystalline SiC molded body with a circular plate diameter of about 100 mm or more and 300 mm or less.
[0005] In addition, regarding the polycrystalline SiC molded body used as a component of a semiconductor manufacturing device, if a film is formed on a rod-shaped substrate, a cylindrical polycrystalline SiC molded body is also preferably used. At this time, the polycrystalline SiC molded body has the growth direction of the CVD film as the main surface. If it is a cylindrical polycrystalline SiC molded body, the surface and the inner surface of the tube can become the main surface. The thickness of the polycrystalline SiC molded body changes with the film forming time and can be formed into any thickness. It is known that there is a polycrystalline SiC molded body with a tube diameter of about 5mm or more and 700mm or less.
[0006] Regarding SiC molded bodies with specific resistivity, Patent Document 1 describes a silicon carbide body for semiconductor manufacturing components, characterized in that it is a silicon carbide body obtained by CVD method, the nitrogen content is 0.1 to 100 ppm, the content of metal elements other than silicon is 10 ppm or less, the resistivity is 0.01 to 10 Ω·cm, and the deviation of the resistivity is 10% or less. As a specific example, a silicon carbide body with a resistivity of 0.1 to 5 Ω·cm is disclosed.
[0007] Patent Document 2 describes an independent article containing chemical vapor deposited low-resistivity silicon carbide having a resistivity lower than 0.9 Ω·cm, and discloses, as a specific example, a silicon carbide deposit having a resistivity of 0.25 to 0.9 Ω·cm.
[0008] Prior art literature
[0009] Patent Literature
[0010] Patent Document 1: Japanese Patent No. 4595153
[0011] Patent document 2: Japanese Patent Application Publication No. 2001-316821. Summary of the invention
[0012] Technical problem to be solved by the invention
[0013] However, as a SiC molded body, since the crystal grain size is small, the usual wear is preferentially carried out from the grain boundary, which is related to the reduction of particulate matter generated during the wear process, and is therefore considered to be preferred. In addition, since the crystal grain size is large, the volume resistivity is reduced, and it can also be preferably used for heaters and other purposes among semiconductor manufacturing equipment parts.
[0014] Therefore, an object of the present invention is to provide a polycrystalline SiC molded body having a crystal grain size controlled within a specific range and a low volume resistivity, and a method for producing the same.
[0015] Technical solutions for solving technical problems
[0016] After research, the inventors found that the above-mentioned problem can be solved by the following method.
[0017] [1] A polycrystalline SiC molded body, wherein the average crystal grain size is 5.5 μm or more and 25.0 μm or less, and the nitrogen concentration is 0.27×10 20 Pieces / cm 3 Above 5.4×10 20 Pieces / cm 3 Below, the product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 / cmVsec or less.
[0018] [2] The polycrystalline SiC molded body according to [1], wherein the volume resistivity is 0.0200 Ω·cm or less.
[0019] [3] A method for manufacturing a polycrystalline SiC molded body as described in [1], the manufacturing method comprising: a step of disposing a substrate in a CVD reactor; a step of heating the substrate; and a step of introducing a mixed gas containing a raw material gas and a nitrogen-containing gas into the CVD reactor to form a polycrystalline SiC film on the heated substrate using a CVD method, wherein the step of forming the polycrystalline SiC film is carried out under the condition that the film formation rate is not less than 15 μm / h and not more than 60 μm / h and the residence time is not less than 10 seconds and not more than 100 seconds.
[0020] Effects of the Invention
[0021] According to the present invention, a polycrystalline SiC molded body having a crystal grain size controlled within a specific range and low volume resistivity and a method for manufacturing the same are provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a schematic diagram showing an example of a production system for a polycrystalline SiC molded body.
[0023] Figure 2 This is a schematic diagram showing a modified example of the CVD reactor. DETAILED DESCRIPTION
[0024] 1. Polycrystalline SiC molded body
[0025] The polycrystalline SiC molded body according to the embodiment of the present invention has an average crystal grain size of 5.5 μm or more and 25.0 μm or less, and a nitrogen concentration of 0.27×10 20 Pieces / cm 3 Above 5.4×10 20 Pieces / cm 3 Below, the product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 By adopting this structure, a polycrystalline SiC molded body with a crystal grain size controlled within a specific range and a low volume resistivity can be obtained.
[0026] In this specification, the "average crystal grain size" refers to the "average crystal grain size" calculated from the "area fraction" determined by EBSD (Electron Backscatter Diffraction).
[0027] According to the present embodiment, a polycrystalline SiC molded body can be obtained, which has an average crystal grain size of 5.5 μm or more and 25.0 μm or less and a nitrogen concentration of 0.27×10 20 Pieces / cm 3 Above 5.4×10 20 Pieces / cm 3 Below, the product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 / cmVsec or less.
[0028] The average crystal grain size is, for example, 5.5 μm or more and 25.0 μm or less, preferably 8.0 μm or more and 20.0 μm or less, and more preferably 10.0 μm or more and 15.0 μm or less.
[0029] In this specification, "nitrogen concentration" refers to the number of nitrogen atoms per unit volume (amount / cm 3 ). The nitrogen concentration was determined using dynamic SIMS (dynamic secondary ion mass spectroscopy).
[0030] The nitrogen concentration was 0.27×10 20 Pieces / cm 3 Above 5.4×10 20 Pieces / cm 3 The following range can obtain a sufficiently small volume resistivity. It should be noted that the nitrogen concentration corresponds to 200 ppm or more and 3800 ppm or less.
[0031] Such a nitrogen concentration as an impurity concentration doped into a polycrystalline SiC molded body can be said to be a very large value, and generally speaking, this is an amount that exceeds the solid solubility limit. When nitrogen is added in an amount exceeding the solid solubility limit, a compound different from SiC will be produced, and thus the function required as a polycrystalline SiC molded body cannot be exhibited. However, according to this embodiment, by the manufacturing method described later, nitrogen can still be solid-dissolved in the presence of such a concentration of nitrogen, so that the characteristics required for the polycrystalline SiC molded body can be met. The reason for achieving such characteristics is not clear, but, for example, it can be considered that when the film formation speed is too slow, since the film formation time becomes longer, the time for producing a compound different from SiC also becomes longer, and it becomes impossible to solid-dissolve. In addition, it can also be considered that when the film formation speed is too fast, since SiC has formed a film before the nitrogen decomposes into a reactive intermediate, the solid solution reaction of nitrogen cannot fully occur.
[0032] The “product of carrier density and Hall mobility” is a value obtained from the “carrier density” and the “Hall mobility”.
[0033] The product of the carrier density and the Hall mobility is related to the volume resistivity. According to the present embodiment, the product of the carrier density and the Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 / cmVsec or less, a sufficiently small volume resistivity can be obtained.
[0034] In addition, the polycrystalline SiC formed body may have a more preferred size of 25×10 20 pcs / cmVsec or more 100×10 20 / cmVsec or less, more preferably 35×10 20 pcs / cmVsec or more 100×10 20 The product of the carrier density below 100 / cmVsec and the Hall mobility.
[0035] “Carrier density” refers to the concentration of impurities doped into a SiC molded body. The carrier density can be obtained using Hall effect measurement.
[0036] For example, the carrier density is 1.0×10 19 Pieces / cm 3 Above 7.0×10 19 Pieces / cm 3 the following.
[0037] The Hall mobility is a well-known parameter that can be determined using Hall effect measurements. For example, the Hall mobility is 10 cm 2 / Vsec above 150cm 2 / Vsec or less.
[0038] According to the present embodiment, the polycrystalline SiC molded body may have a volume resistivity of, for example, 0.0200 Ω·cm or less, preferably 0.0100 Ω·cm or less. In addition, the polycrystalline SiC molded body may have a volume resistivity of more preferably 0.0010 Ω·cm or less, and further preferably 0.0001 Ω·cm or less.
[0039] In a preferred embodiment, the polycrystalline SiC molded body is 3C-SiC.
[0040] In a preferred embodiment, the polycrystalline SiC molded body has a main surface. The polycrystalline SiC molded body is preferably plate-shaped, more preferably disk-shaped. In the case of a plate, the main surface of the polycrystalline SiC molded body refers to the surface and back surface except the side surface. In this case, the thickness of the polycrystalline SiC molded body is, for example, 0.1 mm or more and 5.0 mm or less, preferably 0.2 mm or more and 3.0 mm or less. In addition, in the case of a disk-shaped body, the diameter of the polycrystalline SiC molded body is not particularly limited, for example, 100 mm or more and 300 mm or less, preferably 130 mm or more and 200 mm or less.
[0041] The polycrystalline SiC molded body may also be cylindrical. In the case of a cylindrical shape, the main surface of the polycrystalline SiC molded body refers to the surface and inner surface of the tube. In this case, the thickness of the polycrystalline SiC molded body is, for example, 0.1 mm to 5.0 mm, preferably 0.2 mm to 3.0 mm.
[0042] In a more preferred embodiment, the main surface has a (111) peak intensity ratio of 0.25 to 0.50. "(111) peak intensity ratio" refers to a parameter representing the ratio of the diffraction peak intensity of SiC (111) to the total diffraction peak intensity of SiC (111) surface, SiC (200) surface, SiC (220) surface and SiC (311) surface in an X-ray diffraction pattern.
[0043] 2. Method for manufacturing polycrystalline SiC molded body
[0044] The polycrystalline SiC molded body having the above-mentioned characteristics can be obtained by adjusting the film forming conditions, etc. in the production method described below. Next, the production method of the polycrystalline SiC molded body of the present embodiment will be described.
[0045] Figure 1 1 is a schematic diagram showing an example of a manufacturing system used in the manufacturing method of a polycrystalline SiC molded body of the present embodiment. A CVD reactor 1 and a mixer 2 are provided in the manufacturing system. In the mixer 2, a carrier gas 6, a raw gas 7 as a SiC supply source, and a nitrogen-containing gas 8 are mixed to generate a mixed gas. The mixed gas is supplied to the CVD reactor 1 from the mixer 2 at a "flow rate Q". A substrate 3 (for example, a graphite substrate) is arranged in the CVD reactor 1. In the CVD reactor 1, the substrate 3 is heated during operation. The substrate 3 is preferably in the shape of a disk or a rod. In addition, a nozzle 4 is provided in the CVD reactor 1, through which the mixed gas is introduced into the CVD reactor. After the mixed gas is introduced into the CVD reactor, a polycrystalline SiC film is formed on the heated substrate 3 by the CVD method. At this time, nitrogen from the nitrogen-containing gas is doped into the polycrystalline SiC film. That is, a polycrystalline SiC film doped with nitrogen can be obtained. For the obtained polycrystalline SiC film, the substrate 3 is removed and ground as needed. In this way, a polycrystalline SiC molded body can be obtained.
[0046] in addition, Figure 1 In the example shown, a plurality of nozzles 4 are provided. In addition, the substrate 3 is arranged in the longitudinal direction. The plurality of nozzles 4 are provided on both sides of the furnace wall in a manner of sandwiching the substrate 3. Figure 1 In FIG. 5 , L is the distance between the front end of each nozzle (the outlet for ejecting the raw material gas) and the substrate 3 .
[0047] It should be noted that the CVD reactor 1 is not limited to Figure 1 The structure shown. Figure 2 It is a diagram showing a modified example of the CVD reactor 1 . Figure 2 In the example shown, a plurality of nozzles 4 are arranged at the upper part of the CVD reactor 1. The substrate 3 is arranged horizontally. The CVD reactor 1 may also be Figure 2 The structure shown.
[0048] As embodiments of the CVD reactor, cold wall type, hot wall type, etc. can be considered. In the cold wall type CVD reactor, the furnace wall and the furnace atmosphere are not directly heated, and only the substrate is directly heated. In the hot wall type CVD reactor, the entire furnace including the furnace wall and the furnace atmosphere is heated. In this embodiment, there is no difference in the characteristics of the SiC molded body obtained by the cold wall type and the hot wall type.
[0049] In addition, in the present embodiment, the polycrystalline SiC film is formed within a specific “reaching time τ.” Specifically, the polycrystalline SiC film is formed within a specific “reaching time τ.” Specifically, the polycrystalline SiC film is formed within a specific reaching time τ of 0.02 seconds to 0.10 seconds.
[0050] The arrival time τ represents the time from when the mixed gas is introduced into the CVD reactor until it reaches the substrate. Specifically, the arrival time τ is calculated according to the following formula.
[0051] Arrival time τ = L / u
[0052] L: The distance between the raw gas outlet (nozzle tip) and the substrate
[0053] u: Flow rate of mixed gas in the reactor
[0054] The flow velocity u of the mixed gas is obtained by "flow rate Q / spout cross-sectional area A".
[0055] The flow rate Q represents the flow rate of the mixed gas between the mixer and the reactor. The flow rate Q is not particularly limited, and is, for example, 10 L / min to 400 L / min, and preferably 50 L / min to 350 L / min.
[0056] According to the inventors' understanding, the arrival time τ affects the nitrogen concentration of the solid solution, and also affects the carrier concentration and the Hall mobility. Therefore, by optimizing the arrival time τ, a polycrystalline SiC film having a predetermined average particle size and controlling the nitrogen concentration and the product of the carrier density and the Hall mobility can be achieved. The arrival time τ is preferably 0.02 seconds to 0.10 seconds, and from the perspective of being able to adjust the particle size to the preferred range, it is more preferably 0.02 seconds to 0.08 seconds, and further preferably 0.02 seconds to 0.06 seconds.
[0057] As the raw material gas for the SiC supply source, a single-component system (gas containing Si and C) or a two-component system (gas containing Si and gas containing C) may be used.
[0058] For example, the raw material gas of the single component system includes methyltrichlorosilane, phenyltrichlorosilane, methyldichlorosilane, dimethyldichlorosilane, trimethylchlorosilane, etc. In addition, the raw material gas of the two component system includes a mixture of silane-containing gas such as trichlorosilane and monosilane and hydrocarbon gas.
[0059] The nitrogen-containing gas may be any gas as long as it can dope nitrogen into the polycrystalline SiC film. For example, nitrogen gas is used as the nitrogen-containing gas.
[0060] The carrier gas used in film formation is not particularly limited, and for example, hydrogen gas or the like can be used.
[0061] The film forming conditions other than the reaching time τ are not particularly limited, and for example, the following conditions can be employed.
[0062] Regarding the heating temperature during film formation, the reaction temperature is, for example, 1300° C. to 1400° C., preferably 1300° C. to 1350° C. It should be noted that the furnace wall and the heat insulating material in the furnace are preferably at a temperature that does not deposit SiC and decomposition products of the raw material gas (for example, 1000° C. or less, preferably 700° C. or less).
[0063] The flow rate of the nitrogen-containing gas is, for example, 5 vol% to 100 vol%, preferably 30 vol% to 50 vol%, relative to the total flow rate of the nitrogen-containing gas, the source gas, and the carrier gas.
[0064] The film forming rate is, for example, 15 μm / h to 60 μm / h, preferably 15 μm / h to 40 μm / h. By controlling the film forming rate within the above range, the average particle size and the nitrogen concentration can be controlled to predetermined values.
[0065] The residence time is, for example, 10 to 100 seconds, preferably 20 to 75 seconds. The residence time refers to the time the mixed gas stays in the reactor. By controlling the residence time within the above range, the average particle size can be controlled to a predetermined value.
[0066] [Example]
[0067] The present invention is described in more detail below through examples. It should be noted that in the present example and comparative example, the film forming time is appropriately set to be between 1 hour and 60 hours, and the reaction temperature is appropriately set to be between 1200°C and 1500°C.
[0068] (Example 1)
[0069] As a CVD reactor, we have prepared Figure 1 As a substrate, a graphite substrate with a diameter of 160 mm and a thickness of 5 mm was prepared and placed in the CVD reactor.
[0070] Then, under the conditions described in Table 1, a polycrystalline SiC film is formed on the substrate. Specifically, MTS (methyltrichlorosilane) is used as the raw material gas. H2 gas is used as the carrier gas. N2 gas is used as the nitrogen-containing gas. The raw material gas, the carrier gas and the nitrogen-containing gas are mixed in the mixer 2 to generate a mixed gas. The mixed gas is supplied to the CVD reactor 1. The supply amount of the mixed gas adopts the value recorded as "gas amount" in Table 1. In addition, the concentrations of MTS gas, H2 gas and N2 gas in the mixed gas are as described in Table 1.
[0071] The residence time is 22 seconds. The residence time is calculated by the following formula.
[0072] Residence time (seconds) =
[0073] (furnace volume / gas volume)×((20+273) / (reaction temperature+273))×60
[0074] The arrival time τ is 0.03 seconds.
[0075] After film formation, the graphite substrate was taken out of the CVD reactor and peripheral processing and cutting were performed. The graphite substrate was then removed to obtain a polycrystalline SiC molded body with a diameter of 150 mm and a thickness of 0.6 mm. Then, the surface and back were ground by plane grinding to obtain a polycrystalline SiC molded body with a diameter of 150 mm and a thickness of 0.4 mm. This was obtained as the polycrystalline SiC molded body of Example 1.
[0076] (Examples 2 to 8 and Comparative Examples 1 to 3)
[0077] A polycrystalline SiC film was formed in the same manner as in Example 1. However, the film formation conditions were changed as shown in Table 1.
[0078] (Evaluation Method)
[0079] The (111) peak intensity ratio, carrier density, Hall mobility, nitrogen concentration (SIMS N concentration), average crystal grain size, and resistivity of the obtained polycrystalline SiC molded body were determined. The measurement methods of each value are as follows.
[0080] (111) Peak intensity ratio
[0081] Using XRD-6000 manufactured by Shimadzu Corporation, an X-ray diffraction pattern based on the 2θ / θ method at the center of the polycrystalline SiC molded body was measured under the following conditions.
[0082] Copper Target
[0083] Voltage: 40.0kV
[0084] Current: 20.0mA
[0085] Divergence slit: 1.00000 degrees
[0086] Scattering slit: 1.00000 degrees
[0087] Light receiving slit: 0.30000mm
[0088] Scanning range: above 20.000 degrees and below 80.000 degrees
[0089] Scanning speed: 4.0000 degrees / min.
[0090] Sampling interval: 0.0200 degrees
[0091] Default time: 0.30 seconds
[0092] In the obtained X-ray diffraction pattern, background correction was appropriately performed, and the diffraction peak intensity in the range of the diffraction angle 2θ of 35.3 degrees to 36.0 degrees was determined as the peak intensity of the SiC (111) plane of 3C-SiC.
[0093] Similarly, the diffraction peak intensity in the range of the diffraction angle 2θ of 41.1 degrees to 41.8 degrees was determined as the peak intensity of the SiC (200) plane.
[0094] Similarly, the diffraction peak intensity within the range of the diffraction angle 2θ of 59.7 degrees to 60.3 degrees was determined as the peak intensity of the SiC (220) plane.
[0095] Similarly, the diffraction peak intensity within the range of the diffraction angle 2θ of 71.5 degrees to 72.3 degrees was determined as the peak intensity of the SiC (311) plane.
[0096] Then, the total value of the diffraction peak intensity of the SiC (111) plane, SiC (200) plane, SiC (220) plane and SiC (311) plane is calculated. Furthermore, the ratio of the diffraction peak intensity of SiC (111) to the total value is calculated as the (111) peak intensity ratio.
[0097] (Carrier density, Hall mobility)
[0098] The Hall voltage and the resistivity based on the VanderPauw method were obtained using the Resistest 8200 manufactured by Toyo Technology Co., Ltd., Japan, and the carrier density and Hall mobility (Hall effect measurement) were calculated. The sample was cut into a size of about 10 mm × 10 mm × 0.5 mm and an In electrode was formed, and the Hall effect measurement was carried out under the following conditions.
[0099] Applied magnetic field: 1T
[0100] Applied current: 1.0×10 -6 A
[0101] Measurement temperature: room temperature (295K)
[0102] (Nitrogen concentration)
[0103] The nitrogen content in the polycrystalline SiC molded body was measured using SIMS-4000 manufactured by ATOMIKA Corporation.
[0104] (Average crystal size)
[0105] By the EBSD method, a crystal orientation map of the polycrystalline SiC molded body with respect to the normal direction of the main surface is obtained.
[0106] The measurement conditions are as follows.
[0107] Pretreatment: Chemical Mechanical Polishing
[0108] Device:
[0109] FE-SEM JSM-7900F manufactured by JEOL
[0110] EBSD AZtecHKL manufactured by OXFORD
[0111] Image analysis software: AZtec Crystal
[0112] Measurement conditions:
[0113] Voltage: 20kV
[0114] Tilt angle: 70°
[0115] Measuring area: 800μm×600μm
[0116] Measuring interval: 1.4μm
[0117] Evaluation target crystal system: 3C-type SiC (space group 216)
[0118] In the measurement under the above conditions, if the particles with an average particle size of less than 5.5 μm are measured, the analysis will be unstable and no correct analysis result can be obtained, so this case is judged as "unable to evaluate".
[0119] Using the crystal orientation map obtained by the above measurement, in the entire area (800μm×600μm), for all single areas, the value obtained by dividing the area of the single area by the total area of the observation area multiplied by the value of the area of the single area, and calculate their total value to find the average cross-sectional area of the grains (area fraction method). Find the diameter of the circle with the same area as the average cross-sectional area of the obtained grains, and calculate the average crystal grain size. Specifically, the image analysis software attached to the EBSD device is used for analysis to calculate the average crystal grain size.
[0120] In the crystal orientation map, three locations on the same measurement surface are measured, and the average crystal grain size is calculated for each location. The average value of the three locations is taken as the average crystal grain size of the measurement surface.
[0121] The positional relationship of each crystal orientation map is as follows. Determine the center point of the measurement area in the crystal orientation map of the first point. Starting from this center point, move the field of view in any direction to a point that is 2000μm or more and 4000μm or less as the new center point, and measure the crystal orientation map of the second point. Starting from the center point of the measurement area in the crystal orientation map of the second point, move the field of view to a point that is 2000μm or more and 4000μm or less as the new center point, and measure the crystal orientation map of the third point.
[0122] The front and back surfaces were measured, and the larger of the measured values was taken as the average crystal grain size of the sample, with the threshold value set at 10°.
[0123] (Measurement of volume resistivity)
[0124] The volume resistivity of the polycrystalline SiC molded body was measured by a four-probe method according to JIS K 7194. Specifically, Loresta GP MCP-T610 manufactured by Mitsubishi Chemical Analytical Technology Co., Ltd. was used for the measurement of the volume resistivity.
[0125] (Results Examination)
[0126] As shown in Tables 1 and 2, the polycrystalline SiC molded bodies of Examples 1 to 8 are polycrystalline SiC molded bodies formed under the conditions of a film forming rate of 15 μm / h to 60 μm / h and a residence time of 10 seconds to 100 seconds. As shown in Table 2, the volume resistivity of the polycrystalline SiC molded bodies of Examples 1 to 8 is low. In particular, Examples 2 to 8 have extremely low volume resistivity (specifically, less than 0.0074 Ω·cm). The average crystal grain size of these polycrystalline SiC molded bodies of Examples 1 to 8 is 5.5 μm to 25.0 μm, which is confirmed to be a SiC molded body with a crystal grain size in a specific range. In addition, the nitrogen concentration is 0.27×10 19 Pieces / cm 3 Above 5.4×10 20 Pieces / cm 3 The product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 / cmVsec or less.
[0127] In Comparative Example 1, where the film forming speed is 602 μm / h, the average particle size cannot be evaluated, and the product of the carrier density and the Hall mobility is 3.2×10 20 / cmVsec, which is smaller than that of Examples 1 to 8, and the volume resistivity exceeds 0.0200Ω·cm.
[0128] In Comparative Example 2 in which the film forming rate was 911 μm / h, the average crystal grain size could not be evaluated.
[0129] In addition, in Comparative Example 3 in which the film forming speed was 10 μm / h, the average particle size was 27.3 μm, which was larger than those of Examples 1 to 8.
[0130] [Table 1]
[0131]
[0132] [Table 2]
[0133]
[0134]
[0135] (*)Carrier density × Hall mobility (×10 20 / cmVsec)
[0136] Industrial Applicability
[0137] Since the crystal grain size is large, the volume resistivity is low, and the composite material can be preferably used for applications such as heaters among components for semiconductor manufacturing equipment.
[0138] Explanation of symbols
[0139] 1CVD reactor
[0140] 2 Mixer
[0141] 3. Substrate
[0142] 4 Nozzles
[0143] 5. Flow meter
[0144] 6 Carrier gas
[0145] 7 Raw Gas
[0146] 8 Nitrogen-containing gases.
Claims
1. A polycrystalline SiC molded body, wherein: The average crystal grain size is 5.5 μm or more and 25.0 μm or less. The nitrogen concentration is 0.27×10 20 Pieces / cm 3 Above 5.4×10 20 Pieces / cm 3 the following, The product of carrier density and Hall mobility is 4.0×10 20 pcs / cmVsec or more 100×10 20 / cmVsec or less.
2. The polycrystalline SiC molded body according to claim 1, wherein: The volume resistivity is 0.0200 Ω·cm or less.
Citation Information
Patent Citations
Low resistivity silicon carbide
JP2001316821A